[tex]\displaystyle\bf\\\frac{2}{5} \Big(\frac{5}{6} -\frac{3}{4} x\Big)=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{2}{5} \cdot\frac{5}{6} -\frac{2}{5} \cdot \frac{3}{4} x=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{1}{3} -\frac{3}{10} x=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{3}{10} x+\frac{1}{5} x=\frac{1}{3} -4\frac{1}{3} \\\\\\\frac{3+2}{10} x=-4\\\\\\\frac{5}{10} x=-4\\\\\\\frac{1}{2} x=-4\\\\\\x=-4:\frac{1}{2} =-4\cdot 2=-8\\\\\\Otvet \ : \ -8[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\\frac{2}{5} \Big(\frac{5}{6} -\frac{3}{4} x\Big)=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{2}{5} \cdot\frac{5}{6} -\frac{2}{5} \cdot \frac{3}{4} x=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{1}{3} -\frac{3}{10} x=\frac{1}{5} x+4\frac{1}{3} \\\\\\\frac{3}{10} x+\frac{1}{5} x=\frac{1}{3} -4\frac{1}{3} \\\\\\\frac{3+2}{10} x=-4\\\\\\\frac{5}{10} x=-4\\\\\\\frac{1}{2} x=-4\\\\\\x=-4:\frac{1}{2} =-4\cdot 2=-8\\\\\\Otvet \ : \ -8[/tex]